Detection prospects of light pseudoscalar Higgs boson at the LHC - Monoranjan Guchait; Aravind H. Vijay; Jacky Kumar (Journal of High Energy Physics, 2017)
Abstract The discovery potential of light pseudo scalar Higgs boson for the mass range 10-60 GeV is explored. In the context of the next-to-minimal supersymmetric standard (NMSSM) model, the branching fraction of light pseudo scalar Higgs boson decaying to a pair of photon can be quite large. A pair of light pseudo scalar Higgs boson produced indirectly through the standard model Higgs boson decay yields multiple photons in the final state and the corresponding production rate is restricted by ATLAS data. Discussing the impact of this constraint in the NMSSM, the detection prospects of light pseudoscalar Higgs boson in the channel consisting of at least three photons, a lepton and missing transverse energy are reported. It is observed that the possibilities of finding the pseu-doscalar Higgs boson for the above mass range are promising for an integrated luminosity ℒ $$ \mathrm{\mathcal{L}} $$ = 100fb−1 with moderate significances, which can reach to more than 5σ for higher luminosity options.